Efficacy of topical antibiotic administration on the inhibition of perioperative oral bacterial growth in oral cancer patients: a preliminary study. Issue 10 (October 2015) - Funahara, M.; Hayashida, S.; Sakamoto, Y.; Yanamoto, S.; Kosai, K.; Yanagihara, K.; Umeda, M.
Abstract Parenteral antibiotic prophylaxis is the current standard of therapy in clean-contaminated oral cancer surgery. Nevertheless, the incidence of surgical site infection (SSI) in oral oncological surgery is relatively high, especially in major surgery with reconstruction and tracheotomy. The aims of this study were to investigate the perioperative condition related to microorganisms in the oral cavity and to examine the efficacy of the topical administration of tetracycline in reducing the number of bacteria in the oropharyngeal fluid during intubation. The number of oral bacteria was measured during intubation in patients undergoing major oral cancer surgery. The efficacy of the topical administration of tetracycline or povidone iodine gel in reducing the bacteria was then investigated. Bacteria in the oropharyngeal fluid grew from 106 CFU/ml to 108 CFU/ml during the 3 h after intubation (CFU, colony-forming units). When tetracycline was applied to the dorsum of the tongue, oral bacteria decreased immediately to 105 CFU/ml, and the number of bacteria in the oropharyngeal fluid was maintained below 107 CFU/ml for 7 h. The concentration of tetracycline in the oropharyngeal fluid was extremely high for several hours after topical administration. The topical administration of tetracycline could reduce oral bacteria in patients undergoing clean-contaminated oral cancer surgery. This method is expected to be effective in the prevention of SSI.